Position paper: Using EdTech to support teacher education and professional development in low- and middle-income countries (internal working paper). - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2020)
ZenodoArchiveID: 5652080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652080 2339240:VJNSF4EV 2339240:Z6ZIBS2B 2405685:6E2K4GGE
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _dont_post_PDF

Problem Analysis. A Global Public Good produced by the EdTech Hub - Hennessy, Sara; Jordan, Katy; Haßler, Björn; Hollow, David; Brugha, Meaghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (EdTech Hub, 2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
EdTechHub.Copy: 2129771:9VXUZISD EdTechHub.Copy: 2129771:ADGISTZU EdTechHub.ThisIsNot: 2339240:2387P995 2339240:8RA9UD7W shortDOI: 10/ghgnfz KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2129771:56GZ7UBP 2129771:9VXUZISD 2129771:ADGISTZU 2129771:GYTVIZJV 2129771:MBZLFNDM 2339240:2387P995 2339240:65KP6SVQ 2339240:6FUA4SDV 2339240:85SBE7SC 2339240:8RA9UD7W 2339240:IXIRDBKK 2339240:STPRNPV3 2405685:BBQI3VSA 2405685:CMRISZHV 2405685:F6UAIKKN 2405685:QJTH2UXC 2405685:R88UVQZ7 503888:7EH7BANW 503888:PI9FLM7C
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The relationship between educational television and mathematics capability in Tanzania - Watson, Joseph; Hennessy, Sara; Vignoles, Anna (British Journal of Educational Technology, 2020)
Previous studies have frequently demonstrated that educational television viewing can have a positive effect on learning in low-income country contexts when shows are delivered in controlled settings. However, the consequence of day-to-day viewing in such contexts has scarcely been considered. Additionally, no recent published research has provided any information on the costs of educational television. The lack of research in these areas is striking. Examining educational television viewing in monitored settings provides limited information on the influence of routine television consumption. Further, the broad reach of numerous educational television programmes should provide low perviewer costs and, resultantly, strong cost-effectiveness findings. This PhD study therefore examined (1) the association between educational television exposure and mathematics capability and (2) the cost effectiveness of educational television interventions. To achieve this, research was carried out that centred on Ubongo Kids – a popular Tanzanian-produced show delivering mathematics-focused content.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13047 10.17863/cam.54714 2339240:6LGJJU8F 2339240:MVL3KA6H 2339240:U3SHRB68 2339240:XZDCXAZ7 2405685:8WKWEBZZ 2405685:A5XKUF3W 2405685:CHDUKI36 2405685:VJ8U5IDE 2405685:YENK6ASB
Keywords: Tanzania; ___working_potential_duplicate; cost effectiveness; educational television; mathematics; ⛔ No DOI found

OER4Schools: Outcomes of a sustained professional development intervention in Sub-Saharan Africa - Haßler, Björn; Hennessy, Sara; Hoffmann, R; Makonga, Abel (Frontiers in Education, 2020)
Sustaining educational initiatives beyond short-term pilot projects is highly challenging in low-income countries. We describe the outcomes and implications of our iterative Design-Based Implementation Research conducted in Zambia. This focused on a unique, school-based, peer-facilitated professional learning programme for primary teachers: OER4Schools integrates interactive pedagogy, open digital educational resources and mobile learning. Teacher interviews carried out 18 months after a year-long intervention showed that the programme became self-sustaining; earlier participants reported further development of their interactive teaching strategies and awareness of pupil progress; recent joiners developed similarly. Roles of teachers and pupils changed and a new classroom culture emerged. The study identifies the key mechanisms involved in sustainability, including culturally sensitive and participatory development and implementation, semi-structured multimedia materials, and supportive organisational structures for sustained professional learning. Our findings are hence framed by sociocultural influences as well as the wider policy context.
HHH3A shortDOI: 10/ghgn5x KerkoCite.ItemAlsoKnownAs: 10.3389/feduc.2020.00146 10/ghgn5x 2129771:6KN48Q7A 2339240:A5GQ37WB 2339240:B8J5VSFY 2405685:BG6WTIJK 2405685:BNF58PFR 2405685:KLUBUEJY 2405685:V7S2E5AQ 2405685:VHZVRENG 2534378:M3FT5RN4
Keywords: Author:Haßler; C: Zambia; Culturally responsive pedagogy (CRP); Design-based implementation research; Interactive Pedagogy; Learner-centred pedagogy; School leadership; Sustainable Development Goal (SDG) 4; Teacher Profesisonal Development; Zambia; ___working_potential_duplicate; _yl:b; dode_eth-src-dode; dode_eth-trf2-dode; school improvement; sub-Saharan Africa

Technology in education in low-income countries: Problem analysis and focus of the Hub's work - Hennessy, Sara; Jordan, Katy; Hassler, Bjoern; Hollow, David; Brugha, Meghan; Jamieson Eberhardt, Molly; Sabates, Ricardo (2020)
An output by the EdTech Hub - #EdTechHub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3352007 10/ghgnfz 2339240:EYQWGP5R 2405685:ZGFQHAS3